2019
DOI: 10.2478/jaiscr-2019-0008
|View full text |Cite
|
Sign up to set email alerts
|

Collision-Free Autonomous Robot Navigation in Unknown Environments Utilizing PSO for Path Planning

Abstract: The autonomous navigation of robots in unknown environments is a challenge since it needs the integration of a several subsystems to implement different functionality. It needs drawing a map of the environment, robot map localization, motion planning or path following, implementing the path in real-world, and many others; all have to be implemented simultaneously. Thus, the development of autonomous robot navigation (ARN) problem is essential for the growth of the robotics field of research. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The authors in [42] suggested an adaptive PSO algorithm (APSO) to define the solution for route planning in MR situations that were handled precisely. Krell et al [43]used the PSO and the Gazebo simulator to create an ARN system that can navigate in an unknown environment and reach the predefined target without collisions. The findings demonstrated that in multiple environments with different features, the robot can generate and follow efficiently.…”
Section: Path Planning Meta-heuristic Methodsmentioning
confidence: 99%
“…The authors in [42] suggested an adaptive PSO algorithm (APSO) to define the solution for route planning in MR situations that were handled precisely. Krell et al [43]used the PSO and the Gazebo simulator to create an ARN system that can navigate in an unknown environment and reach the predefined target without collisions. The findings demonstrated that in multiple environments with different features, the robot can generate and follow efficiently.…”
Section: Path Planning Meta-heuristic Methodsmentioning
confidence: 99%
“…The optimization algorithms for pathfinding for ground robotics [20][21][22][23][24], aerial vehicles [25][26][27], and underwater vehicles [28,29] includes a wide range of applications. The most well-known applications for autonomous vehicles are obstacle avoidance, path planning, localization, navigation, sensing, and communication, which works on preessential maps related to the environment; they also play a vital role in communication relay, aviation industry for surveillance, and loitering dominated missions.…”
Section: Scholarly Contributions and Applicationsmentioning
confidence: 99%
“…The fundamental motivation for using meta-heuristic algorithms in this controlling and optimization problem is reliable optimization through the use of a local search strategy and the randomness in their evolutionary processes to find optimal or near-optimal solutions. However, this does not always result in meta-heuristics finding compelling or optimal solutions, as was shown in several cases [33,44,45]. In such a context, exploration and exploitation constitute the fundamental and important processes of meta-heuristic algorithms.…”
Section: Bio-inspired Meta-heuristic Algorithmsmentioning
confidence: 99%